The Dynamics of Psycho-Social-Ecological Resilience in the Urban Environment: A Complex Adaptive Systems Theory Perspective - Stroink, Mirella L. (Frontiers in Sustainable Cities, 2020)
As the proportion of people living in urban areas continues to grow (United Nations, 2019), it becomes increasingly important to understand urban resilience in the face of both chronic and acute, endogenous and exogenous stressors. Indeed, there is a growing literature on urban resilience, which includes several recent frameworks to operationalize and assess the concept and its indicators. Inherent in this literature, though rarely explicitly, is the psychology of the people comprising urban environments. The purpose of this paper is to explore the intersection of urban resilience and psychological resilience by viewing both in the context of complex adaptive systems theory. Arising from this juncture is a more robust and dynamic understanding of resilience, a psycho-social-ecological resilience. The discussion will draw from this notion of resilience a more thorough framework for understanding the reciprocal relationships among urban dwelling people and their total environments. Areas for future research and implications for our understandings of psychological resilience, urban resilience, and sustainable cities will be highlighted.